Pengaruh Metode Kerja Kelompok Pada Pembelajaran Matematika Terhadap Hasil Belajar Siswa Sekolah Dasar - Amara Salsabilla; Mochamad Guntur (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This study aims to see the effectiveness of learning mathematics using the group work method. This is included in the quantitative descriptive research. This research uses a one group pretest posttest design. The research sample is 30 students of SDN 2 Kalibuntu. Data collection is in the form of observational notes regarding observations on student learning activities during learning activities and the teacher's way of managing learning, questionnaires containing student opinions, and test sheets to see student learning outcomes. Analysis of research data using correlation test and t-test techniques. This research shows that teachers get a very good category in managing learning, student activity shows an average of 100%, students get learning outcomes with completeness reaching 75%, and students' positive responses regarding group work methods are 95%. So learning mathematics by applying the group work method is effective in improving student learning outcomes in grades IV-VI at SDN 2 Kalibuntu.